Could the Less-Than Subtotal Parathyroidectomy Be an Option for Treating Young Patients With Multiple Endocrine Neoplasia Type 1-Related Hyperparathyroidism? - Montenegro, Fabio Luiz de Menezes; Brescia, Marilia D'Elboux Guimaraes; Lourenço, Delmar Muniz; Arap, Sergio Samir; d'Alessandro, Andre Fernandes; de Britto e Silva Filho, Gilberto; Toledo, Sergio Pereira de Almeida (Frontiers in Endocrinology, 2019)
Background: The surgical treatment of primary hyperparathyroidism (HPT) in patients with multiple endocrine neoplasia type 1 (MEN1) has evolved due the concern of permanent hypoparathyroidism. As the diagnosis has increased, the extent of operation has decreased. Children and adolescents requiring parathyroidectomy pose a difficult balance to achieve between persistent HPT and life-long hypoparathyroidism. The aim of the present study is to review our experience with a large series of patients with MEN1-related HPT (HPT/MEN1) treated at a single institution in order to find clues to a better treatment decision in these cases.. Method: Retrospective analysis of consecutive HPT/MEN1 cases treated at a single institution with different operations: Total parathyroidectomy and immediate forearm autograft (TPTX-AG), subtotal (STPTX), unintentional less than subtotal (U-LSTPTX) and intentional less than subtotal parathyroidectomy (I-LSTPTX). Results: There were seven (4%) adolescents in 161 cases treated from 1987 to 2018, three underwent TPTX-AG and they are euparathyroid. Four had U-LSTPTX. Two are euparathyroid, one had mild recurrence and still is not candidate to reoperation after 16 years and one had recurrent disease requiring reoperation after 8 years due to the residual gland. Considering 84 initial cases operated on since 2011, the rates of hypoparathyroidism were 30.8% (U-LSTPTX), 28.2% (TPTX-AG), 13.6% (STPTX) and 0% (I-LSTPTX). MIBI scan was more sensitive to show parathyroid glands and bilateral disease. Considering the concordance of MIBI and ultrasound for the possibility of unilateral clearance, it would be suitable to 22.6% of the cases. Intra-operative parathormone showed a significant decay even after unilateral exploration, but longer follow up is necessary. Conclusions: Younger patients are becoming more frequent as candidates to parathyroidectomy in the last years. Less extensive procedures should be planned based on carefully preoperative imaging. MIBI scintigraphy should be performed in such cases as it has more sensitivity to disclose multiple and bilateral hyperfunctional parathyroid glands. Patients and their relatives should be fully informed of the risks and benefits during consent process. Future research with larger cohorts and long-term results are necessary to clarify if less than subtotal parathyroidectomy is adequate in selected groups such as children and adolescents.